Peran Organisasi Misdinar dalam Pembentukan Karakter dan Iman Remaja - Alfridus Yorianto Sasi; Emmeria Tarihoran (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
This study provides an overview of the role of the church in facilitating Catholics, especially children and adolescents. The role of the church in question is by providing assistance to the altar server organization group. Child assistance carried out by facilitating spiritual activities can foster in children a spirit of service, thus forming a positive character in children from an early age. The purpose of this study was to determine the extent to which activities carried out in the altar server organization have an impact on the formation of children's character. The method used in this study is qualitative with a case study approach. The research data in the form of altar server member assistance activities and juxtaposed with findings from previous studies which then become references to strengthen the study in this study. The findings in this study indicate that with assistance for children and adolescents, it will foster a spirit of service and create responsible individuals so that it can influence the formation of positive character.